Strategic Communication in Politics : Griffin’s Rhetoric Theory on Bobby Nasution’s Campaign - Olga Wansyan; Olvi Prihutami Sihombing; Rita Hartati (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research aims to analyze Bobby Nasution’s campaign speech using Aristotle’s rhetorical proofs and Griffin’s Theory of Strategic Communication. The study investigates rhetorical proofs of logos, ethos, and pathos and explores their application in political communication. This qualitative research utilized content analysis with data derived from the transcript and video of Bobby Nasution’s speech, titled